Enhancing power quality in high-power renewable applications using a new extendable nine-level grid-tied converter - Shivam Kumar Yadav; Bhim Singh (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
This paper introduces a new multilevel converter configuration for integrating large solar plants with an 11 kV grid tailored for a megawatt scale. This configuration employs twelve switches with a symmetrical progression, resulting in nine levels in phase voltage. Consisting of main power modules (MPM) and extension power modules(EPMs), this modular system effectively manages solar power. This paper elucidates various states and operational modes, highlighting each level's flawless performance and emphasizing configuration's scalability to accommodate additional power modules. The discussion initiates with a comprehensive exploration of the converter's operation, followed by its grid-tied fundamental control. Test cases are presented to assess system's performance in varying solar conditions. Converter employs polynomial-based selective harmonics elimination (SHE) to switch at fundamental frequency, ensuring efficiency in steady-state and dynamic conditions. Finally, new solar converter undergoes rigorous testing in Simulink, highlighting its superior dynamics for grid-tied operations. Moreover, simulated results are validated in a laboratory real-time test bench.